Distance of 6-Minute Walking Test in Acute Myocardial Infarction and Its Influecing Factors - Putu Karsiani; Deddy Tedjasukmana; Marulam M Panggabean (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: To know the result of a 6 minute walking distance (MWD) test in patients with acute myocardial infarction, characteristic of the subjects and the relationship between the 6 MWD test and factors such as age, body weight, body height and type of the infarct.Methods: The subjects of this study were stable acute myocardial infarction patients. Baseline data which included age, body weight, body height, blood pressure, heart rate, saturated oxygen, dyspnea scale measured with Borg scale and chest pain (numeric rating scale) were collected before doing the 6MWD test. After doing the test without warming up, the blood pressure, heart rate,oxygen saturation,dyspnea scale (Borg scale) and chest pain (numeric rating scale) were recorded.Results: From 49 subjects enrolled in this study, three dropped out (n=46). The mean of 6 MWD test was 208.50 (100-400) meter or 44.31% from predicted. There was a correlation between distance of 6 MWD and body height with r=0.302; p=0.04 (p<0.05) and also between female gender and type of infarct which was NSTEMI with B=-92.3; p=0.02 (p<0.05) and B= -77.004; p=0.01 (p<0.05).Conclusions:The mean distance of 6 MWD test was 208.5 m. There was significant correlation body height, female gender and NSTEMI type of infarction.Keywords : 6 minute walking distance test, distance of 6 minute walking, functional test, acute